Passive Cushiony Biomechanics of Head Protection in Falling Geckos - Hao Wang; Wenbo Wang; Yi Song; Lei Cai; Zhendong Dai (Applied Bionics and Biomechanics)
Gekko geckos are capable to crawl on the steep even on upside-down surfaces. Such movement, especially at great altitude, puts them at high risks of incidentally dropping down and inevitable body or head impactions, though they may trigger air-righting reaction (ARR) to attenuate the landing shocks. However, the air-righting ability (ARA) in Gekko geckos is not fully developed. The implementation of ARR in some geckos is quite slow; and for those without tails, the ARR is even unobservable. Since ARA is compromised in Gekko geckos, there must be some other mechanisms responsible for protecting them from head injuries during falls. In this study, we looked into a Gekko gecko’s brain to study its internal environment and structure, using the magnetic resonance imaging (MRI) technique. The results showed that the brain parenchyma was fully surrounded by the cerebrospinal fluid (CSF) in the skull. A succulent characteristic was presented, which meant the intracalvarium was significantly occupied by the CSF, up to 45% in volume. Then a simplified three-dimensional finite element model was built, and a dynamic simulation was conducted to evaluate the mechanical property of this succulent characteristic during the head impactions. These implied the succulent characteristic may play certain roles on the self-protection in case of head impaction, which is adaptable to the Gekko gecko’s locomotion and behavior.